No difference in genotype frequencies of polymorphisms of the nitric oxide pathway between Caucasian normal and high tension glaucoma patients - Weiß, Johanna; Fränkl-Braun, Stephan; Flammer, Josef; Haefeli, Walter E. (Molecular vision, 2012)
Purpose - Substantial evidence suggests that ocular perfusion is regulated by nitric oxide (NO), and polymorphisms in genes encoding for enzymes involved in NO formation and degradation (endothelial nitric oxide synthase [NOS3] and cytochrome b-235 alpha polypeptide gene [CYBA]) might contribute to vascular dysregulation observed in glaucoma. We therefore assessed the association of glaucoma with polymorphisms of NOS3 and CYBA previously associated with cardiovascular disease. We also compared the distribution of these polymorphisms in patients with high tension glaucoma (HTG) and normal tension glaucoma (NTG) and evaluated its association with vascular dysregulation in a subset of glaucoma patients. - - Methods - Three hundred Caucasian patients with HTG and 127 with NTG were enrolled in the study and genotyped for G894T (rs1799983) and T-786C (rs2070744) in NOS3 and C242T (rs4673) in CYBA. - - Results - None of these polymorphisms had a different allele or genotype distribution between HTG and NTG patients nor had the presence of vasospasms any impact. - - Conclusions - We studied the frequencies of a set of relevant polymorphisms of the NO system in a large cohort of glaucoma patients and found no association. These results therefore suggest the absence of a relevant relationship with different glaucoma forms in Caucasians.
Gesehen am 09.05.2019